Diamond dilemma : shaping Korea for the 21st century - Hussain, Tariq
Political planning |z Korea (South) 651 _0 |a Korea (South) |x Politics and government |y 2002- 651 _0 |a Korea (South) |x Economic policy |y 1988- 651 _0 |a Korea (South) |x Economic conditions |y 1988-